The c.859G>C variant in the SMN2 gene is associated with types II and III SMA and originates from a common ancestor. Issue 9 (24th June 2010) - Bernal, S; Alías, L; Barceló, M J; Also-Rallo, E; Martínez-Hernández, R; Gámez, J; Guillén-Navarro, E; Rosell, J; Hernando, I; Rodríguez-Alvarez, F J; Borrego, S; Millán, J M; et al.
Abstract : Homozygous mutations of the telomeric SMN1 gene lead to degeneration of motor neurons causing spinal muscular atrophy (SMA). A highly similar centromeric gene (SMN2) can only partially compensate for SMN1 deficiency. The c.859G>C variant in SMN2 has been recently reported as a positive disease modifier. We identified the variant in 10 unrelated chronic SMA patients with a wide spectrum of phenotypes ranging from type II patients who can only sit to adult walkers. Haplotype analysis strongly suggests that the variant originated from a common ancestor. Our results confirm that the c.859G>C variant is a milder SMN2 allele and predict a direct correlation between SMN activity and phenotypic severity.